037 Successful ABO and HLA incompatible renal transplantation in children in the united kingdom over the last decade. (December 2018) - Hew, EY; Mamode, N; Kessaris, N; Christian, M; Dudley, J; Milford, D; Tse, Y; Webb, NJA; Stojanovic, J; Marks, SD
Abstract : Introduction: There is increasing evidence of good short and medium term outcomes for ABO incompatible (ABOi) and HLA incompatible (HLAi) with pre-transplant positive crossmatches in paediatric practice. However, there are concerns regarding the higher risks of infective complications and antibody-mediated rejections. The aim of this paper is to show that the short-term outcomes for ABOi and HLAi renal transplantation are comparable to (ABOc/HLAc) compatible renal transplants in children in the UK. Methods: Data were obtained from the UK Transplant Registry (NHS Blood and Transplant) on all children (aged <18 years) who received a first living paediatric kidney only transplant between 1 January 2006 and 31 December 2016 from 10 paediatric transplant centres. Baseline demographic data were collected of 709 first living paediatric kidney only transplants, of which 23 were ABOi and 4 were HLAi. Estimated glomerular filtration rate (eGFR) was calculated using plasma creatinine at three months post-transplant. Comparisons of graft function following transplantation were made between ABOi, HLAi, and ABOc/HLAc compatible groups. Results: Pre-emptive transplantation occurred in 35% and 25% of ABOi and HLAi recipients with delayed graft function in 3%, 6% and 0% of ABOc/HLAc, ABOi and HLAi respectively with no cases of primary non-function. Renal allograft survival was 100% in each group although there was one death of ABOi pRTR with a functioning graft. For ABOi transplants (n=16), the median and inter-quartile range (IQR) eGFR was 88 (63 – 150) mls/min/1.73 m 2 . The eGFR in ABOc/HLAc group had a median (IQR) of 101 (74 – 144) mls/min/1.73 m 2 . No statistically significant difference was found between these transplant groups due to the small number of patients. Conclusion: The short term outcomes from this follow-up have shown that ABOi and HLAi renal transplantation are possible for paediatric renal transplant recipients in situations where no compatible donors are available.